Non‐vitamin K antagonist oral anticoagulants versus vitamin K antagonists in atrial fibrillation patients with previous stroke or intracranial hemorrhage: A systematic review and meta‐analysis of observational studies - Guo, Zongwen (Clin Cardiol, 2021)
Several observational studies have compared the effectiveness and safety outcomes between nonvitamin K antagonist oral anticoagulants (NOACs) and vitamin K antagonists (VKAs) in atrial fibrillation (AF) patients with a history of either stroke/transient ischemic attack (TIA) or intracranial hemorrhage. Therefore, our current meta‐analysis aimed to address this issue. The Cochrane Library, PubMed, and Embase databases were systematically searched until December 2020 for all relevant observational studies. We applied a random‐effects model to pool adjusted hazard ratios (HRs) and 95% confidence intervals (CIs) for this meta‐analysis. A total of 10 studies were included. Among patients with a history of stroke/TIA, the use of NOACs versus VKAs was associated with decreased risks of stroke (HR, 0.82, 95% CI 0.69–0.97), systemic embolism (HR, 0.73, 95% CI 0.61–0.87), all‐cause death (HR, 0.87, 95% CI 0.81–0.94), major bleeding (HR, 0.77, 95% CI 0.64–0.92) and intracranial hemorrhage (HR, 0.54, 95% CI 0.38–0.77). Among patients with a history of intracranial hemorrhage, the use of NOACs versus VKAs was associated with reduced risks of stroke (HR, 0.81, 95% CI 0.68–0.95), all‐cause death (HR, 0.68, 95% CI 0.49–0.94), and intracranial hemorrhage (HR, 0.66, 95% CI 0.51–0.84). Compared with VKAs, the use of NOACs exhibited superior efficacy and safety outcomes in AF patients with previous stroke/TIA, and the use of NOACs was associated with reduced risks of stroke, all‐cause death, and intracranial hemorrhage in patients with a history of intracranial hemorrhage.